Improvement and shelf life extension of fresh creams chocolate filling for Tolaal Enterprise - Hussain, Norhayati; Abdul Razak, Raihana; Mohamad, Nur Sadrina; Karim, Roselina (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Tolaal Enterprise started to supply food & catering services as the founder, Hj Hamidun had 30 years expertise in the food catering industry. When Hj Hamidun passed away in 2010, her daughter Aznida took the lead & added the chocolate section to the catering services as the chocolate industry in Malaysia is rising. They are facing problems associated with fillings softening and short shelf life (less than 2 weeks) with the use of fresh fruit puree. Based on the above mentioned problems, it is necessary to develop suitable formulation of mango and pineapple fresh cream fillings to be inserted into milk chocolate shell. Thus, the approach of our present study is to increase the viscosity of fillings by adding five different hydrocolloids (Xanthan gum, Guar gum, Carboxy Methyl Cellulose, Locust Bean gum and Pectin) from 0 to 1g/100g (w/w) concentration as a thickener to ensure that longer shelf life and better texture is made available to meet the expectations of the consumer. The suitable hydrocolloid at optimum concentration is expected to contribute high quality filled milk chocolate containing mango and pineapple purees after storage at suitable storage conditions. Thus, the making of milk chocolate with fresh fillings can be expanded to help increase the profits of the company.